Climate Regimes, El Nino-Southern Oscillation and Meningococcal Meningitis Epidemics - Olusegun Steven Ayodele Oluwole (Frontiers Media S.A., 2015)
Meningoccocal meningitis is a major public health problem that kills thousands annuallyin Africa, Europe, North and South America. Occurrence is, however, highest during thedry seasons in Sahel Africa. Interannual changes in precipitation correlate with interannualchanges in El Nino-Southern Oscillation (ENSO), while interdecadal changes in precipita-tion correlate with Pacific Decadal Oscillation (PDO). The objective of the study was todetermine if there is spectral coherence of seasonal, interannual, and interdecadal changesin occurrence of meningococcal meninigitis in Sahel, Central, and East Africa with interan-nual and interdecadal changes of PDO and ENSO. Time series were fitted to occurrence ofmeningocococcal meningitis in Sahel, Central, and East Africa, to indices of precipitationanomalies in the Sahel, and to indices of ENSO and PDO anomalies. Morlet wavelet wasused to transform the time series to frequency-time domain. Wavelet spectra and coherenceanalyses were performed. Occurrence of meningococcal meningitis showed seasonal, inter-annual, and interdecadal changes. The magnitude of occurrence was higher during warmclimate regime, and strong El Ni nos. Spectra coherence of interannual and interdecadalchanges of ENSO and PDO with occurrence of meningococcal meningitis in Sahel, Central,and East Africa were significant at p < 0.0001. Precipitation in Sahel was low during warmclimate regimes. Spectra coherence of changes in precipitation in Sahel with ENSO wassignificant at p < 0.0001. ENSO and PDO are determinants of the seasonal, interannual,and interdecadal changes in occurrence of meningococcocal meningitis. Public health man-agement of epidemics of meningococcal meningitis should include forecast models of changesin ENSO to predict periods of low precipitation, which initiate occurrence.